Biodistribution and Pharmacokinetic Analysis of Combination Lonidamine and Paclitaxel Delivery in an Orthotopic Animal Model of Multi-drug Resistant Breast Cancer Using EGFR-Targeted Polymeric Nanoparticles - Milane, Lara (2011)
The aim of this study was to assess the biodistribution and pharmacokinetics of epidermal growth factor receptor (EGFR)-targeted polymer blend nanoparticles loaded with the anticancer drugs lonidamine and paclitaxel. Plasma, tumor, and tissue distribution profiles were quantified in an orthotopic animal model of multi-drug resistant (MDR) breast cancer and were compared to treatment with non-targeted nanoparticles and to treatment with drug solution. Poly(D,L-lactide-co-glycolide)/poly(ethylene glycol)/EGFR targeting peptide (PLGA/PEG/EFGR peptide) construct was synthesized for incorporation in poly(ε-caprolactone) (PCL) particles to achieve active EGFR targeting. An isocratic HPLC method was developed to quantify lonidamine and paclitaxel in mice plasma, tumors, and vital organs. The targeted nanoparticles demonstrated superior pharmacokinetic profile relative to drug solution and non-targeted nanoparticles, particularly for lonidamine delivery. The first target site of accumulation is the liver, followed by the kidneys, and then the tumor mass; maximal tumor accumulation occurs at 3 hours post-administration. Lonidamine/paclitaxel combination therapy administered via EGFR-targeted polymer blend nanocarriers may become a viable platform for the future treatment of MDR cancer.